An investigation on THz yield from laser-produced solid density plasmas at relativistic laser intensities. (12th June 2018) - Herzer, S; Woldegeorgis, A; Polz, J; Reinhard, A; Almassarani, M; Beleites, B; Ronneberger, F; Grosse, R; Paulus, G G; Hübner, U; May, T; Gopal, A
Abstract: We experimentally characterize the generation of high-power terahertz radiation (THz) at the rear surface of a target irradiated by multiple laser pulses. A detailed dependence of the THz yield as a function of laser pulse duration, energy, target material and thickness is presented. We studied the THz radiation emitted mainly in two directions from the target rear surface, namely target normal (acceptance angle 0.87 sr) and non-collinear direction (perpendicular to the target normal direction—acceptance angle 4.12 sr). Independent measurements based on electro-optic diagnostics and pyroelectric detector were employed to estimate the THz yield. Most of the energy is emitted at large angles relative to the target normal direction. THz yield increases with incident laser intensity and thinner targets are better emitters of THz radiation compared to thicker ones.